Castilla y León - Spain in a smaller size; An analyse of collective identities and wish for autonomy - Roland Brandtjen (IU Internationale Hochschule, 2024)
Spain has been known for several years for its ethnic and separatist debate. This work aims to examine the extent to which the potential for conflict in Spain as a whole can also be found on a small scale, i.e. in one of Spain's autonomous communities. The largest autonomous community in terms of area, Castilla y León, which also consists of the most provinces, was chosen for this purpose. It is questionable whether such strong autonomy movements exist not only in Spain but also in Castilla y León. Do certain isms exist or are they just purely theoretical scientific concepts? This paper attempts to examine and fill a scientific gap on this topic by means of an adapted quantitative survey. From 2020 and 2023, these surveys have been conducted in Castilla y León. They are analysed by descriptive statistics. The paper concludes with a Conclusion and the bibliography.
Keywords: 650; Identity; Autonomy; Castilianism; Leonesism; Survey